Causal nexus between health and economic development: Evidence among OIC high-income economies - Zurina Kefeli@ Zulkefli; Zaidi M.A.S.; Wahab A.A.O.A. (Universiti Putra Malaysia, 2024)
The effects of health on economic development have been discussed in depth in the literature. Most of the findings have shown that the economic performance of a country can be enhanced by improving the health of the citizens. This paper investigates the causal link between health and economic development of high-income economies of selected OIC countries. Since these countries also have high expenditure on health in comparison with other OIC countries, the findings would give some indication of the importance of having high spending in health for the economic wellbeing of a country. The Toda-Yamamoto Granger non-causality model was used on data spanning from 1970 to 2015, and the results showed mixed causal relationships. Specifically, some countries like Bahrain and Kuwait have a health condition that boosts economic development, while Saudi Arabia experiences the opposite effect. However, health and economic development have bidirectional causality in the United Arab Emirates, while Brunei, Oman and Qatar do not show any causal direction between health and economic development. The findings give some evidence of the importance of health on economic prosperity without disregarding the fact that economic development is also important for good health. Universiti Putra Malaysia Press.